Assessment of risk factors for overweight and obesity among school going children in Kanpur, Uttar Pradesh - Watharkar, Atul; Nigam, Seema; Nigam, Seema; Martolia, Dinesh Singh; Varma, Punit; Barman, SK; Sharma, RP (Indian Journal of Community Health, 2015)
Background: Adolescent obesity is one of the most serious public health challenges of the 21st century. The problem is global and is steadily affecting many low and middle-income countries, particularly in urban settings. Objective: To determine risk factors for overweight and obesity among school going children of age group 12-15 years in Kanpur. Method: A cross-sectional study was conducted from September 2013 to August 2014 among students of age group 12-15 years in four schools of Kanpur that were selected by using multistage random sampling. Sample size was 806. The information about dietary habits and physical activity pattern was obtained by direct interview method. Height and weight were measured using standard techniques for the same and BMI was calculated. Student who had BMI >85th and <95th percentile of reference population were classified as overweight and BMI for age >95th percentile of reference population were classified as obese. Results: The prevalence of obesity and overweight was 3.97% and 9.80% respectively and consuming fast foods and carbonated drinks regularly, low levels of physical activity, watching television for more than 2 hours per day or playing computer games for more than 2 hours per day were significantly associated with overweight and obesity. Conclusion: Unhealthy dietary habits and sedentary lifestyle are the major risk factors for overweight/ obesity in adolescents. Intervention measures focusing mainly on increasing the physical activity, decreasing consumption of energy dense foods and providing psychological support is essential to fight this new emerging problem of obesity in adolescents.